2021
DOI: 10.3389/fmolb.2021.699443
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the GXXXG/A Motifs in the Human Na+/Taurocholate Co-Transporting Polypeptide NTCP on Its Bile Acid Transport Function and Hepatitis B/D Virus Receptor Function

Abstract: Homodimerization is essential for plasma membrane sorting of the liver bile acid transporter NTCP and its function as Hepatitis B/D Virus (HBV/HDV) receptor. However, the protein domains involved in NTCP dimerization are unknown. NTCP bears two potential GXXXG/A dimerization motifs in its transmembrane domains (TMDs) 2 and 7. The present study aimed to analyze the role of these GXXXG/A motifs for the sorting, function, and dimerization of NTCP. The NTCP mutants G60LXXXA64L (TMD2), G233LXXXG237L (TMD7) and a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Although, during revision of the manuscript, three independent cryo-EM structures of human NTCP were published [13][14][15], partly with bound viral myr-preS1 peptide, the precise molecular interactions between the host-derived NTCP receptor and the HBV surface proteins are still not fully understood. Experimental approaches, such as protein engineering and computational biology methods, are powerful tools in exploring motifs within the NTCP protein that are essential for regulation of its HBV affinity during infection [3,9,10,12,23,24,32,33]. In this study, we identified a novel NTCP tyrosine-enriched motif 139YIYSRGIY146 that is significantly involved in the regulation of NTCP-HBV preS1 interactions and, thus, in the control of NTCP receptor function (Figure 7A,B).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although, during revision of the manuscript, three independent cryo-EM structures of human NTCP were published [13][14][15], partly with bound viral myr-preS1 peptide, the precise molecular interactions between the host-derived NTCP receptor and the HBV surface proteins are still not fully understood. Experimental approaches, such as protein engineering and computational biology methods, are powerful tools in exploring motifs within the NTCP protein that are essential for regulation of its HBV affinity during infection [3,9,10,12,23,24,32,33]. In this study, we identified a novel NTCP tyrosine-enriched motif 139YIYSRGIY146 that is significantly involved in the regulation of NTCP-HBV preS1 interactions and, thus, in the control of NTCP receptor function (Figure 7A,B).…”
Section: Discussionmentioning
confidence: 90%
“…It was demonstrated that N5A/N11A and N5Q/N11Q double mutants lacking both N-glycosylation sites of NTCP were transport negative for bile acids and showed markedly diminished NTCP-driven HBV entry into hepatocytes. As N-glycosylation generally alters the dimerization properties of proteins [22], and NTCP dimerization normally occurs early in the sorting process of the protein towards the plasma membrane [23][24][25], changes in the glycosylation status of NTCP could fundamentally affect its proper sorting to the plasma membrane, where NTCP fulfills its transporter and receptor functions.…”
Section: Introductionmentioning
confidence: 99%
“…Single mutations, deletions, and fragment replacements within the NTCP/Ntcp sequence have identified numerous regions and residues that define the protein structure, topology and its functionality. As depicted in Table 1 , those studies were mainly focused on: (i) Na + -dependent bile acid uptake and substrate specificity [ 20 , 33 , 40 , 46 , 48 , 64 , 65 , 66 , 67 , 68 ], (ii) HBV/HDV receptor function [ 9 , 13 , 33 , 34 , 40 , 63 , 68 , 69 , 70 , 71 , 72 ], (iii) cellular localization and protein trafficking [ 33 , 39 , 40 , 64 , 65 , 73 , 74 ], (iv) posttranslational modifications [ 33 , 34 , 39 ], (v) oligomerization [ 63 , 71 , 75 , 76 ], and (vi) the presence of conserved motifs or functional domains [ 13 , 39 , 62 , 64 , 67 , 71 , 77 ].…”
Section: Protein Engineering As a Valuable Approach To Study Ntcp Functionsmentioning
confidence: 99%
“…The largest number of them examined residues that participate in bile acid transport. According to previous reports, amino acids located at the N-terminal part of NTCP/Ntcp, such as D24, C44, G60, A64, Q68, S105, N106, D115, S119 have been reported to markedly regulate the bile acid transport function [ 66 , 71 , 75 , 78 ]. Moreover, strong evidence suggests that transmembrane domain VIII, which is localized in the “core” domain, is essentially involved in the bile acid transport activity.…”
Section: Protein Engineering As a Valuable Approach To Study Ntcp Functionsmentioning
confidence: 99%
See 1 more Smart Citation